2022
DOI: 10.1093/sleep/zsac079.856
|View full text |Cite
|
Sign up to set email alerts
|

0862 A unique case of severe sleep onset and maintenance insomnia following COVID-19 vaccination

Abstract: Introduction The COVID-19 vaccines have documented transient side effects, including injection site soreness, redness, headache, fatigue, and fever. In addition, there have been few reported long-term side effects, including Guillain-Barre, pericarditis, and cerebral venous sinus thrombosis. We present a rare case of severe insomnia as a long-term side effect following COVID-19 vaccination. Report of Cases: A 59-year-old female with a past medical history of well-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Around 7.6% and 38% of people complained about trouble in sleeping for more than half days and several days respectively. There were around 50% of people who had no issue with their sleep cycle 17 . As in a study it was concluded that chronic insomnia and sleep deprivation could be a side effect of the Covid'19 vaccination 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Around 7.6% and 38% of people complained about trouble in sleeping for more than half days and several days respectively. There were around 50% of people who had no issue with their sleep cycle 17 . As in a study it was concluded that chronic insomnia and sleep deprivation could be a side effect of the Covid'19 vaccination 19 .…”
Section: Discussionmentioning
confidence: 99%